Entrepreneurial orientation in companies in the garment manufacturing sector in Cajamarca - Portal-Díaz, Pedro M. (2021)
Objective. To determine the level of entrepreneurial orientation in the manufacturing sector of the garment manufacturing sector in the city of Cajamarca, during the year 2019. In this study, five dimensions were evaluated: autonomy, innovation, risk taking, proactivity and competitive aggressiveness. Methods. The type of research is basic, nonexperimental design and cross-sectional. The study population consisted of 12 companies in the manufacturing sector, garment manufacturing in the city of Cajamarca. The data collection technique was the survey and the questionnaire was used as an instrument, consisting of 20 questions, with 4 items for each dimension. Results. Entrepreneurs have 100 % autonomy, 100 % risk taking, 96 % innovation, 83 % proactivity and a medium level of competitive aggressiveness with 44 %. Conclusions. The level of entrepreneurial orientation of companies in the manufacturing sector, garment manufacturing, is 79 %; corresponding to a high level since, in 4 of 5 dimensions, those of entrepreneurial orientation, the entrepreneurs demonstrate a high level of entrepreneurial orientation. These dimensions are autonomy, proactivity, risk-taking and innovation; while competitive aggressiveness shows a low level with respect to the first four dimensions.